PENGARUH WAKTU PENYIMPANAN DAN VOLUME EKSTRAK DAUN SELEDRI DALAM PEMBUATAN YOGHURT SELEDRI - Ajeng Surya Aprilia; Aurellia Chusnul Azizah; Faidliyah Nilna Minah (jurnal ATMOSPHERE, 2024)
Celery (Apium Graveolens L.) is a plant from the Apiaceae family which is widely used as a vegetable and fresh vegetables to complement food, especially on the stems and leaves of celery. Yogurt is one of the longest fermented milk products and is quite well known in all countries, has a shape similar to ice cream porridge but the taste of yogurt itself has a slightly sour taste. In this study several stages were used, namely optimization of fat content with variations in volume of 37, 47, 56, 66, and 75 mL of celery leaf extract solution mixed with other ingredients such as plain yogurt with storage times of 3, 6, 9, 12, and 15 days , to determine the quality of celery yogurt products, the quality parameters observed included fat content, ash content, metal content, microbial test, and organoleptic test. So that from the results of the test method and the purpose of this research is to determine the effect of storage time and volume of celery leaf extract on the manufacture of celery yogurt.